Mild parenchymal lung disease and/or low diffusion capacity impacts survival and treatment response in patients diagnosed with idiopathic pulmonary arterial hypertension. Issue 6 (4th June 2020) - Lewis, Robert A.; Thompson, A.A. Roger; Billings, Catherine G.; Charalampopoulos, Athanasios; Elliot, Charlie A.; Hamilton, Neil; Hill, Catherine; Hurdman, Judith; Rajaram, Smitha; Sabroe, Ian; Swift, Andy J.; Kiely, David G.; et al.
There are limited published data defining survival and treatment response in patients with mild lung disease and/or reduced gas transfer who fulfil diagnostic criteria for idiopathic pulmonary arterial hypertension (IPAH). Patients diagnosed with IPAH between 2001 and 2019 were identified in the ASPIRE (Assessing the Spectrum of Pulmonary Hypertension Identified at a Referral Centre) registry. Using prespecified criteria based on computed tomography (CT) imaging and spirometry, patients with a diagnosis of IPAH and no lung disease were termed IPAHno-LD (n=303), and those with minor/mild emphysema or fibrosis were described as IPAHmild-LD (n=190). Survival was significantly better in IPAHno-LD than in IPAHmild-LD (1- and 5-year survival 95% and 70% versus 78% and 22%, respectively; p<0.0001). In the combined group of IPAHno-LD and IPAHmild-LD, independent predictors of higher mortality were increasing age, lower diffusing capacity of the lung for carbon monoxide ( D LCO ), lower exercise capacity and a diagnosis of IPAHmild-LD (all p<0.05). Exercise capacity and quality of life improved (both p<0.0001) following treatment in patients with IPAHno-LD, but not IPAHmild-LD . A proportion of patients with IPAHno-LD had a D LCO <45%; these patients had poorer survival than patients with D LCO ≥45%, although they demonstrated improved exercise capacity following treatment. The presence of even mild parenchymal lung disease in patients who would be classified as IPAH according to current recommendations has a significant adverse effect on outcomes. This phenotype can be identified using lung function testing and clinical CT reports. Patients with IPAH, no lung disease and severely reduced D LCO may represent a further distinct phenotype. These data suggest that randomised controlled trials of targeted therapies in patients with these phenotypes are required. Patients with IPAH who have mild parenchymal lung disease have significantly worse outcomes, in terms of survival and treatment response, when compared to patients with IPAH who do not have evidence of parenchymal lung disease http://bit.ly/3agkYn0